O que o Estado quer dizer quando fala sobre COVID-19: a adesão dóxica em narrativas presidenciais e ministeriais de respostas ao cenário da pandemia - Rafael Borim-de-Souza; João Gabriel Dias dos Santos; Camilla Atibaia Cestari (Ciências Sociais Unisinos)
This research was developed aiming: to analyze, in Brazil, through narratives from the Presidents of the Republic and Ministers of State, what the State wanted to say when it talks about answers to the pandemic scenario provoked by the COVID-19; and, to identify, in this conjuncture, a possible process of doxic adhesion to the answers presented by and in the name of the State. The Bourdieusian sociology was considered as theoretical support to the concepts of State, talking, saying and doxic adhesion. The realized research is applied, qualitative, descriptive, documental and of narratives. It was considered as documents 122 videos published in the channels “Planalto” and “TV BrasilGov”, both on YouTube, in which totalize 3165 minutes of duration. In the matters of the present research, the presidential and ministerial narratives: are analyzed and interrogated as real object; describe expressions and interactions; and, comprehend moral constructions. By consequence, it was recognized the President of the Republic and the Ministers of State as homo narrans, whom narratives were apprehended in a collective sense of argumentation and narration. Lastly, it was analyzed that the State wanted to say economy-jobs when it talks about economy-jobs and/or about health-lives; and, doxic adhesion to the dominant discourse which officializes the State’s answers to the pandemic was identified.